Combination of pharmacotherapy and lidocaine analgesic block of the peripheral trigeminal branches for trigeminal neuralgia: a pilot study - Fabrizio Di Stani; Christine Ojango; Demo Dugoni; Luigi Di Lorenzo; Salvatore Masala; Roberto Delfini; Gianluca Bruti; Giovanni Simonetti; Elcio Juliato Piovesan; Andrea Gennaro Ruggeri (Arquivos de Neuro-Psiquiatria)
Classical trigeminal neuralgia (CTN) is treated predominantly by pharmacotherapy but side effects and unsuccessful occurs. The current study was carried out to evaluate the therapeutic effect of combination of pharmacotherapy and lidocaine block. Thirteen patients with CTN managed with pharmacotherapy were recruited and assigned either to no additional treatment (Group I) or to additional analgesic block (Group II). The primary endpoint was the reduction in the frequency of pain episodes in a month assessed at 30 and 90 days. Comparisons of measurements of pain, general health and depression scales were secondary endpoints. The results from the follow-up visits at 30 and 90 days showed the Group II to have larger reduction in the frequency of pain and exhibited a bigger improvement in the scores of the pain, general health and depression scales. The results from this preliminary study suggest a clinical benefit of the combination of pharmacotherapy and lidocaine block.